KEPUASAN ANGGOTA ATAS PELAYANAN KOPERASI PETANI PADI DI PROVINSI LAMPUNG - H.L, Dyah Aring; Masyhuri, Masyhuri; Mulyo, Jangkung H. (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
This study aims to analyze non-economic benefits (satisfaction) received by rice farmers as member of cooperatives, namely Koptan/KUD measured by member satisfaction level to services provided by koptan/KUD in Lampung Province. The research location is determined in three districts with the highest number of koptan and KUD and the biggest rice producing centers in Lampung Province, namely Central Lampung, South Lampung, and East Lampung. From each district are taken two koptan and two KUD purposively. The size of total farmer sample is 50 people for koptan and 47 people for KUD. Data are analyzed descriptively and by Importance-Performance Analysis method. The results show that member satisfaction of koptan and KUD still need to be improved. The members of koptan and KUD hope that they feel satisfaction in high level for all services given by koptan and KUD. In fact, member satisfaction for service in the RAT, in the payment of mandatory savings, and in the utilization of business units are in a moderate level. Meanwhile member satisfaction in business certainty and welfare is in low level.